2006
DOI: 10.1271/bbb.50552
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity of Bound-Form Phenolics in Potato Peel

Abstract: Free and bound-form phenolics were isolated from potato (cv. Toyoshiro) flesh and peel. The free and bound-form phenolics in the peel showed high DPPH radical scavenging activity, while those in the flesh showed low activity. The total amount of chlorogenic acid and caffeic acid in the free-form phenolics from the peel was highly correlated with the DPPH radical scavenging activity. Ferulic acid was identified as the active radical scavenging compound in the bound-form phenolics from the peel. The potato peel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 13 publications
9
80
1
Order By: Relevance
“…In all cases, TPC in unpeeled potato samples are higher than in peeled samples, showing clearly that TPC is accumulated in the skin tissue. Similar results were also obtained by AlSaikhan et al (1995), Reyes et al (2005), and Nara et al (2006). According to Nara et al (2006), TPC in the flesh and skin have different compositions.…”
Section: Total Phenolic Contentsupporting
confidence: 87%
“…In all cases, TPC in unpeeled potato samples are higher than in peeled samples, showing clearly that TPC is accumulated in the skin tissue. Similar results were also obtained by AlSaikhan et al (1995), Reyes et al (2005), and Nara et al (2006). According to Nara et al (2006), TPC in the flesh and skin have different compositions.…”
Section: Total Phenolic Contentsupporting
confidence: 87%
“…Potato peel has a high content of phenolic compounds, to which antioxidant activity is attributed (Kanatt et al, 2005;De Sotillo et al, 1994). The main components were identified as chlorogenic acid and caffeic acid in free-form phenolics (Kanatt et al, 2005) and ferulic acid in bound-form phenolics (Nara et al, 2006). Potato peel extract can be used as a natural antioxidant in soy bean oil (Rehman et al, 2004) and has been shown to retard lipid oxidation in radiation-processed lamb meat (Kanatt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bound phenolics were assayed in the AIS using a reported procedure (Nara et al, 2006). Each AIS (500 mg) was suspended with 1 M NaOH (20 ml) and shaken overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of radical scavenging activity The DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity was measured by a reported technique (Nara et al, 2006). To a microplate, 50 µl of a sample diluted with 50% ethanol solution and 150 µl of 0.1 mM DPPH/50% ethanol solution were added; the microplate was shaken at room temperature for 30 min, and the absorbance at 540 nm was measured using a microplate reader (Biorad Model 680).…”
Section: Analysis Of Ws and Its Neutral Sugar Compositionmentioning
confidence: 99%